2019
DOI: 10.21307/jofnem-2019-018
|View full text |Cite
|
Sign up to set email alerts
|

Control of Meloidogyne incognita in sweetpotato with fluensulfone

Abstract: In California, sweetpotato is mostly grown on light sandy soils in Merced County. Root-knot nematodes (Meloidogyne spp.) can reduce sweetpotato yields and quality. Fluensulfone is the active ingredient of the new non-fumigant nematicide Nimitz. Unlike fumigant nematicides, toxicity toward non-target organisms is low, and it does not emit volatile organic compounds which negatively impact air quality. In two field trials, the effect of fluensulfone on M. incognita levels, and on the yield and quality of sweetpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Similar results of reduced root-galling of tomato in M. javanica-infested fields were obtained by the application of 4.14 kg ha −1 fluensulfone via drip tapes [80]. The amount of marketable sweet potato in M. incognita-infested fields was increased 1.9-3.4 times by fluensulfone (1.96-3.36 kg ha −1 ) [81]. However, the control efficacy of the compound seems to be lower against nematodes from other genera.…”
Section: Field Application Efficacy and Environmental Conditionssupporting
confidence: 70%
“…Similar results of reduced root-galling of tomato in M. javanica-infested fields were obtained by the application of 4.14 kg ha −1 fluensulfone via drip tapes [80]. The amount of marketable sweet potato in M. incognita-infested fields was increased 1.9-3.4 times by fluensulfone (1.96-3.36 kg ha −1 ) [81]. However, the control efficacy of the compound seems to be lower against nematodes from other genera.…”
Section: Field Application Efficacy and Environmental Conditionssupporting
confidence: 70%
“…Marketable yield was increased for both treatments of fluensulfone, but similarly to results from potato ( Grabau et al, 2019 ), final soil population densities of M. incognita were 8 to 13 times higher than initial population densities. However, Ploeg et al (2019) found that both fluensulfone treatments were able to reduce M. incognita eggs/g of sweet potato root by 80%, which could contribute to the increased marketable yield.…”
Section: Efficacy Of New Chemical Nematicides In Greenhouse and Fieldmentioning
confidence: 91%
“…However, both Telone II and fluensulfone resulted in end of harvest final nematode population densities that were greater than initial densities of nematodes. Ploeg et al (2019) explored the effects of fluensulfone and application timing of fluensulfone on suppression of M. incognita on sweet potato. Fluensulfone was applied at 3.36 kg/ha 2 to 7 days pre-plant, followed by 2 post-plant applications of 1.68 kg/ha at 26 and 58 days.…”
Section: Efficacy Of New Chemical Nematicides In Greenhouse and Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the new nematicides is fluensulfone, which belongs to the heterocyclic fluoroalkenyl sulfones, a new chemical family . Its nematicidal activity is very high, especially against Meloidogyne species, in the laboratory and under field conditions . However, efficacy is affected by nematode species or populations, and soil type .…”
Section: Introductionmentioning
confidence: 99%